The Effect of Flexible Working Space, Flexible Working Hours and Self Efficacy on The Performance of Interior Designers in South Jakarta - Kurniawan, Rudi Ade; Krisnandi, Herry; Digdowiseiso, Kumba (Ridwan Institute, 2024)
This study investigates the impact of Flexible Working Space, Flexible Working Hours, and Self-Efficacy on the performance of interior designers in South Jakarta. Employing an associative research approach, the research incorporates qualitative data processed quantitatively. The primary data source is obtained through purposive sampling, involving a population of 100 individuals with a 95% significance level and a standard deviation of 25%. The findings reveal that flexible working space exerts a positive and significant influence on designer performance. Additionally, flexible working hours demonstrate a positive and significant impact on designer performance. Moreover, self-efficacy is found to positively and significantly affect designer performance. These insights are derived from the analysis of data through multiple linear regression techniques, utilizing the Statistical Product and Service Solution (SPSS) Program version 25. In conclusion, this research underscores the pivotal role of flexible working conditions and self-efficacy in enhancing the performance of interior designers. The positive correlations identified emphasize the importance of adapting workplace structures and fostering self-belief for optimal professional outcomes in this field.